Praktik Jual Beli Sistem Cash On Delivery Pos Indonesia: Ditinjau Dari Hukum Ekonomi Syariah - Saroh Patun Nisa; M Hasan Bisyri; Naili Sa'adah (Fakultas Syariah Universitas Islam Negeri (UIN) K.H. Abdurrahman Wahid Pekalongan, 2021)
The practice of buying and selling the Cash On Delivery (COD) Pos Indonesia system is carried out by the seller sending the buyer's ordered goods first through the Postal expedition service, after the goods arrive in the hands of the buyer, the buyer pays it to the courier who delivered the goods. Furthermore, in the event that the delivery of the results of the payment is made by the Post to the seller's postal checking account through the Pospay application. However, in practice, payments often occur that are not included in the seller's postal checking account, this causes a loss to one party, namely the seller. The purpose of this study was to determine the practice of buying and selling with COD Pos in terms of Islamic Economic Law. This type of research is field research with a qualitative approach. Sources of data in the form of primary and secondary data, primary data obtained by interview and observation techniques while secondary data obtained from other sources such as books, journal articles, interviews and other information that will be discussed by the researcher as a supporter. The subjects of this research are COD Pos providers and COD Pos users, while the object is settlement in accordance with sharia economic law in buying and selling contracts. And data analysis using descriptive qualitative. This study can be concluded that in the implementation of the sale and purchase of COD Pos this has fulfilled the pillars and conditions in buying and selling, but the purpose of the terms of sale and purchase is to bring benefit and not harm one party has not been fulfilled.